2006
DOI: 10.1590/s0103-90162006000600010
|View full text |Cite
|
Sign up to set email alerts
|

Capture of hypothenemus hampei ferrari (coleoptera, scolytidae) in response to trap characteristics

Abstract: Traps lured with semiochemical have been proposed to manage the coffee berry borer, coffee planting is however made under several environmental conditions that may affect the efficacy of traps. Several trap designs and variations were proposed and, therefore, a series of field experiments was carried out to capture coffee berry bores in traps disposed in a low density coffee plantations in the Northern part of the State of Paraná, Brazil. Traps were composed of plastic bottles (2 L) with a window (13 × 18 cm).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 11 publications
3
31
1
7
Order By: Relevance
“…Several types of traps have been proposed trying to optimize beetle capture (Silva et al 2006b, Barrera et al 2006. Since insects also respond to visual stimuli and interactions between visual and chemicals responses may occur (Silva et al 2006a), the development and evaluation of trapping systems to each particular target species could be an important approach in an integrated strategy for CBB management (Mathieu et al 1997). Failures in the massive control of the CBB (Morales -personal observation, Barrera et al 2006) have showed the importance of the improvement of trap effi ciency and have highlighted the need for more detailed studies on the conditions under which traps could be adequately used in the fi eld.…”
mentioning
confidence: 99%
“…Several types of traps have been proposed trying to optimize beetle capture (Silva et al 2006b, Barrera et al 2006. Since insects also respond to visual stimuli and interactions between visual and chemicals responses may occur (Silva et al 2006a), the development and evaluation of trapping systems to each particular target species could be an important approach in an integrated strategy for CBB management (Mathieu et al 1997). Failures in the massive control of the CBB (Morales -personal observation, Barrera et al 2006) have showed the importance of the improvement of trap effi ciency and have highlighted the need for more detailed studies on the conditions under which traps could be adequately used in the fi eld.…”
mentioning
confidence: 99%
“…Entretanto, Borbón-Martinez, Mora-Alfaro e Gonzales (2000), registraram capturas 7,5 vezes maiores em armadilhas brancas do que em vermelhas. Capturas similares da broca-do-café foram obtidas quando se compararam armadilhas de garrafas transparentes, verde-transparentes e vermelhas (SILVA; VENTURA; MORALLES, 2005). Além das cores, o fundo que determina o contraste com a cor da armadilha é fator importante na atratividade da broca (MATHIEU et al, 1997b).…”
Section: Estímulos Visuaisunclassified
“…Neste caso, foram utilizadas garrafas plásticas de 2 L verde-transparentes. Entretanto, Moralles et al (2005) testaram o uso de 30 e 35 armadilhas transparente por ha, mas não conseguiram manter as populações do inseto abaixo do nível de dano econômico, apesar de tê-las reduzido. Redução no número de frutos brocados, grãos quebrados e com outros defeitos e melhoria na qualidade da bebida, em estudo realizado durante 20 meses, foram relatados pela utilização de armadilha (LIMA et al 2004).…”
Section: Papel No Manejounclassified
“…Sabe-se que as fêmeas da broca-do-café são atraídas por compostos à base de álcool (Silva et al, 2006). Esses álcoois podem ser utilizados em armadilhas, para atrair e matar fêmeas adultas.…”
Section: Introductionunclassified
“…Esses álcoois podem ser utilizados em armadilhas, para atrair e matar fêmeas adultas. Vários modelos de armadilhas têm sido utilizados nos experimentos de monitoramento da broca-do-café, com destaque para: garrafa Pet vermelha (Fernandes et al, 2011), Ecoiapar (Silva et al, 2006;Dufour & Frérot, 2008), garrafa transparente modificada (Uemura-Lima et al, 2010) e Brocap (Dufour & Frérot, 2008). Dos modelos apresentados, o de garrafa Pet é o mais simples, e a cor vermelha está entre as mais atrativas.…”
Section: Introductionunclassified